Energy development in rural China toward a clean energy system: utilization status, co-benefit mechanism, and countermeasures - Shi Yin; Shi Yin; Zheng Zhao (Frontiers in Energy Research, 2023)
In order to promote the construction of a clean, low-carbon, and diversified modern rural new energy system, this study examines the development, utilization, connection, and system construction of rural new energy in China. This is done through the classification, integration, and systematic analysis of official statistical data and materials from recent years. Utilizing descriptive statistical analysis, the study holds great theoretical and practical significance. The findings indicate the following: 1) overall, the development of new energy in China’s rural areas is progressing well. However, there is an increasing contradiction between supply and consumption. 2) The new energy industry is experiencing overall growth, accompanied by increasing policy support. Despite this, the industry’s driving effect is not substantial. 3) The development of new energy production equipment in rural areas is lagging, resulting in insufficient cleanliness of energy consumption. There is still a significant gap compared to the goal requirements of agricultural and rural modernization. 4) During the process of rural new energy connection and development, there exists a lack of strong connections between the various subjects of interest. The interest relationship is consequently unstable, necessitating the improvement of a closely-knit interest community. Taking the issue of rural new energy development as its starting point, this paper thoroughly explores the mechanisms driving rural new energy connection. It delves into the interest relationship between the different stakeholders and provides guidelines for optimizing rural new energy system construction. Ultimately, this research aims to contribute to rural revitalization, facilitate the realization of the “double carbon” goal, and establish a modern rural new energy system.